A financial econometric analysis of E-Commerce stock price predictability / Kok-Boon Oh and Sardar M. N. Islam - Kok-Boon, Oh; M N Islam, Sardar (Research Management Institute (RMI), 2012)
The predictability of stock price changes has been a contentious issue in finance for a long period of time. Using the Australian e-commerce financial data for determining the equity value of e-commerce firms, this paper provides an empirical analysis of the issue of predictability of stock prices. The factors contributing to the predictability of equity prices in the e-commerce markets are identified, analyzed and the issues and implications are discussed and explained. This paper presents new approaches to econometric specification, estimation and testing in relation to e-commerce stock predictability including stationarity tests, co-integration modeling and analyses. The policy implications of the empirical findings are stated. The empirical findings of the Australian study are extrapolated and inferences are made for other countries.